Institutional Ownership, Audit Quality, Gender Diversity and Political Connection to Tax Aggressiveness in Indonesia - Fachrul Ananto Firdaus; Siti Nurlaela; Endang Masitoh (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2021)
This study aims to empirically prove the influence of Institutional Ownership, Audit Quality, Gender Diversity, and Political Connection to Tax Aggressiveness. This study used a sample of companies listed on the LQ 45 Indonesia Stock Exchange during the period 2013 – 2019. The sample usage in this study was 13 LQ 45 companies with purposive sampling og 91 sampels during 2-13 – 2019 listed on the Indonesia Stock Exchange. The research method used in this study was the panel data regression model. The results showed that the quality of audits had a positive effect and political connections negatively influenced tax aggressiveness while institutional ownership an gender diversity had no effect on tax aggressiveness.